Phytotherapeutics of Polyphenolic‑loaded Drug Delivery Systems: A Review - Habbu, Prasanna; Hiremath, Mahesh; Madagundi, Smita; Vankudri, Rashmi; Patil, Basavraj; Savant, Chetan (Pharmacognosy Reviews)
Phytopharmaceuticals stand out as recent promising candidates for the treatment of chronic diseases. Nanotechnology has become an important part of pharmaceutical industry, since it involves the development of novel drug delivery systems (nanomedicines) for the benefit of human health. The usefulness of nanotechnology has also been extended to natural products where, number of efforts is made for improvisation of bioavailability and therapeutic potential of polyphenolic compounds. A variety of novel drug delivery systems have been developed for polyphenolic compounds to enhance the relative bioavailability. The developed formulations have also shown sustain or prolonged release properties and also target delivery as evidenced by in-vitro and in-vivo studies. The novel formulations of Quercetin, Green tea catechins, epigallocatechin gallate, Genistein, Resveratrol, Breviscapine and Scutellarin etc. have been prepared by novel techniques and found to increase the therapeutic efficacy against various diseases. The present review focuses on various novel formulations developed for polyphenolic compounds including their therapeutic applications.
Keywords: Polyphenolic compounds; quercetin; rutin; resveratrol; nanotechnology; novel formulations